2016
DOI: 10.1093/jac/dkw220
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: triple therapy combining a proton-pump inhibitor, amoxicillin and metronidazole forHelicobacter pylorifirst-line treatment

Abstract: PAM was less efficacious than clarithromycin-including triple therapies. However, its efficacy was similar to that of PAC when drugs were administered for 14 days, although ITT cure rates did not reach 90%. Use of 14 day, thrice daily and high-metronidazole-dose PAM treatments markedly increased the cure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 143 publications
1
23
1
5
Order By: Relevance
“…9 A large metaanalysis of more than 90 trials demonstrated an eradication rate of up to 70% with this regimen when used as first-line treatment, which was significantly lower compared with clarithromycin triple therapy with amoxicillin (70% vs 77%, p<0.002) or clarithromycin triple therapy with metronidazole (66% vs 78%, p=0.0003). 56 However, eradication rates for amoxicillin-based triple therapy depend highly on metronidazole resistance rates, and further analysis identified longer treatment durations and higher amoxicillin and metronidazole doses (every 8 hours) as factors closely associated with the improved efficacy of amoxicillin-based triple therapy. When high doses were administered for 14 days, eradication rates for amoxicillin-based triple therapy were similar to first-line treatment regimens.…”
Section: Qtc-interval Prolongationmentioning
confidence: 99%
“…9 A large metaanalysis of more than 90 trials demonstrated an eradication rate of up to 70% with this regimen when used as first-line treatment, which was significantly lower compared with clarithromycin triple therapy with amoxicillin (70% vs 77%, p<0.002) or clarithromycin triple therapy with metronidazole (66% vs 78%, p=0.0003). 56 However, eradication rates for amoxicillin-based triple therapy depend highly on metronidazole resistance rates, and further analysis identified longer treatment durations and higher amoxicillin and metronidazole doses (every 8 hours) as factors closely associated with the improved efficacy of amoxicillin-based triple therapy. When high doses were administered for 14 days, eradication rates for amoxicillin-based triple therapy were similar to first-line treatment regimens.…”
Section: Qtc-interval Prolongationmentioning
confidence: 99%
“…Puig et al 80 performed a systematic review and meta-analysis to evaluate the efficacy of triple therapy including a PPI, amoxicillin, and metronidazole in areas with moderate-to-high resistance to clarithromycin. Ninety-four studies (7974 patients) were included.…”
Section: A Combined Strategy: Increasing Duration Of Treatment Prementioning
confidence: 99%
“…Although this regimen is, overall, 30% less effective in metronidazole-resistant strains, highdose 14-day schedules partially overcome the resistance effect. 80…”
Section: Regarding Efficacy In Resistant Bacteria In Patients Harboringmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-quality meta-analysis examined the efficacy of triple therapy with amoxicillin and metronidazole which showed that while overall they were less efficacious than clarithromycin-based regimens (70% vs 77%), efficacy was similar when drugs were administered for 14 days (80% vs 84%). 9 An Italian study looked at the effect of PPI dose and found eradication rates improved from 73.9% to 81.9% when double dose (40 mg esomeprazole) twice daily was used compared to standard (20 mg) dosing. 10 In terms of safety, a Japanese study of 322 patient showed a 15% incidence of diarrhea and 2% risk of skin rash.…”
Section: Triple Therapymentioning
confidence: 99%